To win and lose a Medieval battle - Villalon, L. J. Andrew.
1 online resource.
Keywords: In To Win and Lose a Medieval Battle: Nájera (April 3, 1367). A Pyrrhic Victory for the Black Prince , L.J. Andrew Villalon and Donald J. Kagay provide a full treatment of one of the major battles of the Hundred Years War, which, perhaps because it was fought in Spain, is lesser known to scholars and general readers. Drawing information from contemporary European chronicles and the massive documentary collections of Spanish and French archives, the authors have painstakingly investigated the Iberian and European background events to Nájera and have in minute detail laid out how the army of Enrique II of Castile (assisted by Bertand de Guesclin) and that of his half-brother, Pedro I of Castile (assisted by Edward, the Black Prince), clashed at Nájera on April 3, 1367.